Overview and latest advances in fumonisins - Gordon S. Shephard (Revista Mexicana de Micología, 2005)
Since they were first identified in 1988, the fumonisins have attracted considerableinternational attention due to their carcinogenic properties and almost universal naturaloccurrence in maize and maize-based products. This review, based on a presentation to theFirst Pan-American Symposium on Mycotoxins for Industry, will briefly deal with their fungalproduction, natural occurrence, toxicology and recent international assessment. The currentstatus of methods available for their analytical determination, including extraction, clean-upand chromatographic separation steps will be highlighted, as well as the more rapid methodsfor the determination of total fumonisin based on immunological recognition.Chromatographic methods currently available for the determination of fumonisins includeofficial methods based on high-performance liquid chromatography (HPLC) separation offluorescent derivatives, screening methods based on thin layer chromatography (TLC) andadvanced research methods based on liquid chromatography-mass spectrometry (LC-MS)